PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KINERJA KEUANGAN PADA BSI REGION MEDAN - Yusti Laila; Mutiah Khaira Sihotang (Journal of Sharia Economics, 2022)
This study aims to determine the effect of financial literacy and financial inclusion on financial performance in the region medan BSI. The data collection technique in this study used a questionnaire which is in the from of a data collection technique which is carried out by providing questions ang written statements to respondents to be answered. The population in this study was all employees in the BSI Medan Region. The sample was taken using a saturated sampling technique (total sampling) with a total of 17 employees. The conclusion of the financial inclusion research affects financial performance, financial literacy affects finances, simultaneously financial literacy ang financial inclusion affects financial performance in BSI Medan Region. Keywords: Financial Literacy; Financial Inlusion; Financial Performance.